2006
DOI: 10.1521/soco.2006.24.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype Directionality and Attractiveness Stereotyping: Is Beauty Good or is Ugly Bad?

Abstract: Dion, Berscheid, and Walster (1972), in their seminal article, labeled the attribution of positive characteristics to attractive people the "beauty-is-good" stereotype. The stereotyping literature since then provides extensive evidence for the differential judgment and treatment of attractive versus unattractive people, but does not indicate whether it is an advantage to be attractive or a disadvantage to be unattractive. Two studies investigated the direction of attractiveness stereotyping by comparing judgme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
3
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(194 citation statements)
references
References 61 publications
14
163
3
6
Order By: Relevance
“…8,9 Therefore, the procedure differs from those commonly used in psychological investigations, where two-dimensional records are used. 11,12,22,26,27 Additionally, we tried to link measurements to ratings: even if the human visual system possesses a better sensitivity than the current measurement methods, 11,28 health professionals cannot rely only on perception, but they need objective data for their diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Therefore, the procedure differs from those commonly used in psychological investigations, where two-dimensional records are used. 11,12,22,26,27 Additionally, we tried to link measurements to ratings: even if the human visual system possesses a better sensitivity than the current measurement methods, 11,28 health professionals cannot rely only on perception, but they need objective data for their diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a beautiful face becomes the key to success. 10,21,22 Furthermore, each human face is individually determined, carrying information that allows the identification of the single person. Even among attractive faces, there is a wide variety of facial characteristics that do not repeat the same standard.…”
Section: Introductionmentioning
confidence: 99%
“…Initial attraction is characterized by the willingness to interact/positivity (positive feelings towards someone and disposition to interact with him/her from the first moment), physiological reactions (level of arousal experienced by a person towards another), and flirting/fantasizing behaviours (a pattern of thought that stirs one's imagination and sexuality towards someone) (Rodrigues & Garcia-Marques, 2006). Overall, the influence of biological and cultural factors leads to a greater disposition to experience attraction for the opposite gender (Griffin & Langlois, 2006;Rodrigues & Garcia-Marques, 2005).…”
Section: From Physical Appearance To Eye Sizementioning
confidence: 99%
“…These gender differences may be related to biological and cultural factors (Gangestad, Hasselton, & Buss 2006;Griffin & Langlois, 2006), leading to a greater capacity to experience attraction for individuals of the opposite gender (Rodrigues & Garcia-Marques, 2005). Additionally, the factor structure of the scale suggests the existence of two dimensions of attraction (i.e., physiological reactions and flirting behaviour) sexually oriented and typically associated with feelings towards the opposite gender.…”
Section: The Role Of Eye Size and Observer Gender On Initial Attractimentioning
confidence: 99%
“…Similarly, studies and meta-analyses assert that there is widely-held judgment that people who are beautiful are also more morally upright (26). When subjects were shown a photograph of a person and asked questions about the pictured individual, it was revealed that those who are attractive were assumed to be "more giving, helpful, intelligent, friendly" and these stereotypes exist even in children as young as 7-9 years (27). …”
Section: The Advantages Of Being Beautiful In Social Lifementioning
confidence: 99%